FAKTOR-FAKTOR YANG MEMPENGARUHI PERILAKU IBU NIFAS DALAM MENGKONSUMSI TUO NIFARÖ DI KECAMATAN LOTU KABUPATEN NIAS UTARA - Bernike Sofia Zega; Linda T Maas; eddy syahrial (Kebijakan, Promosi Kesehatan dan Biostatiskik, 2015)
Tuo nifarö istypicalofNiasdrink that contains alcohol that resulted from distillation of cocoa. Tuo nifarö can be utilizedfor many purposes, one of them usedfor post-partum period treatment. The aim of this research is to knowing the determinant of post-partum mother’s behavior who consumedtuonfaroin Lotu, District of North Nias. This kind of researchis descriptivequantitative andqualitative approachto completethe required datawith a sample of 52 people. The resultsof research onthe characteristics ofrespondents,59.6% were25-35years and61.5% of respondentshavea loweducation level. 61.5% of post-partummothers have the moderate trust levelson benefit ofconsumingtuo nifarö. In terms ofnormativebelief, theconsumptionof alcoholic beveragessuch astuo nifarö for post-partum mothers is affected bythe role offamiliesand communitiesthatinfluence the post-partum mothersto act. Attitudetowardconsumption of tuo nifarö 53.8% wereatmoderatelevels. In terms ofaction, 55.8% of respondentsconsumealcoholic beveragespostpartum, where82.8% had a loweducational level, 48.3% have the confidenceandgood judgment, and 58.6% at a moderate level, 100% supportedbyfamiliesand89.7% are supportedby the community. 72.4% of respondentshadconsumedblack beer as a substitutefor various reasons. This occasion should be maintained with regard to alcohol content, and health workers need to explore the benefits of taking tuo nifarö Keywords: determinant, behavior, post-partum mothers, tuo nifarö